Computerization of white collar jobs - Marcus Dillender; Eliza C. Forsythe (W.E. Upjohn Institute for Employment Research, 2019)
We investigate the impact of computerization of white-collar jobs on wages and employment. Using online job postings from 2007 and 2010-2016 for office and administrative support (OAS) jobs, we show that when firms adopt new software at the job-title level they increase the skills required of job applicants. Furthermore, firms change the task content of such jobs, broadening them to include tasks associated with higher-skill office functions. We aggregate these patterns to the local labor-market level, instrumenting for technology adoption with national measures. We find that a 1 standard deviation increase in OAS technology usages reduces employment in OAS occupations by about 1 percentage point and increases wages for college graduates in OAS jobs by over 3 percent. We find negative wage spillovers, with wages falling for both workers with no college experience and college graduates. These losses are in part driven by high-skill office occupations. These results are consistent with technological adoption inducing a realignment in task assignment across occupations, lending office support occupations to become higher skill and hence less at risk from further automation. In addition, we find that total employment and wages per population increase with technological adoption, indicating average gains from computerization that are unequally distributed across the labor market.
Keywords: J23; J24; J31; O33; 330; computerizations; job postings; office and administrative; task content; technology adoption; skill; wages